Implementasi Penyelesaian Permasalahan Algoritma Ascent Hill Climbing Pada Puzzle-8 - Mardiansyah, Yopy; Rizki, Sestri Novia (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
A puzzle is an arrangement of numbers consisting of nine squares that are neatly arranged in a sequence of numbers 1 to number 8. Puzzle games are interesting, fun games and improve cognitive abilities, how to think quickly and are able to develop children's brains to increase their grasping power in solving a problem. . The problem that occurs in this study is the lack of children's ability to solve the logic of compiling puzzles, so make rules and steps to quickly complete this game. The main purpose of this research is to help children improve their thinking patterns so they can arrange numbers 1 to 8 with fast time and solutions. The method used is the Best First Search algorithm in finding the Final Goal quickly and easily. The final result of this research, after several stages of eating, the final result is that the puzzle sequence has fulfilled the final goal according to the initial data. The basic concept of solving the Best First Search Algorithm must follow the rules that have been set by running the process in accordance with existing procedures. If in the search process an unsuitable arrangement is found, then proceed with the next search until it finds the correct position in the form of a sequence of numbers 1 to 8. If it is found, the search algorithm is stopped